2017
DOI: 10.1007/s10006-017-0619-0
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation with LED and laser in repair of mandibular socket rabbit: clinical evaluation, histological, and histomorphometric

Abstract: It was found that photobiomodulation with LASER and LED presented effects. However, only the LED demonstrated a beneficial effect on the process of bone repair in the dental alveoli of rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Photobiomodulation from LED increases bone metabolism and accelerates fracture healing. Our results corroborate findings in other research studies [ 38 , 59 , 64 ], which have also found evidence of the optimization of bone repair in fractures in a period prior to 30 days.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Photobiomodulation from LED increases bone metabolism and accelerates fracture healing. Our results corroborate findings in other research studies [ 38 , 59 , 64 ], which have also found evidence of the optimization of bone repair in fractures in a period prior to 30 days.…”
Section: Resultssupporting
confidence: 93%
“…GelMA increases bone tissue due to its inherent bioactivity and physicalchemical adaptability [69], and due to its porous architecture, it promotes migration, proliferation and osteogenic and chondrogenic differentiation [13,70]. In studies reported by Comunian et al and Ekizer et al [43,64], who evaluated photobiomodulation in bone repair, it was verified that this modality enabled the improvement of neoformation and the quality of the formed bone tissue. This is because photobiomodulation promotes the increased synthesis of the number of osteocytes, collagen and DNA synthesis, proliferation and the differentiation of osteoblasts, in addition to cell metabolism [43,44].…”
Section: In Vivo Experimentsmentioning
confidence: 94%
“…On the topic of our review, among the 17 papers taken into account, nine were performed using animal models [54][55][56][57][58][59][60][61][62]. However, the animals investigated were prevalently rats [54][55][56][57][58][59] and in two cases, rabbits [60,61]; a dog model was surprisingly employed only in one recent work [62].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in accordance with Schropp [9], studies with at least 8 weeks of follow-up could better describe the effect of PBM on bone healing and its possible resorption. Concerning the wavelengths, it is not strange that the only two studies [61,68] that showed no effect of PBM in animal and human models used wavelengths below 800 nm. It is known that wavelengths in the range of 800-980 nm allow better tissue penetration [82,83] than lower and higher ones, and can reach a deeper therapy target, such as bone.…”
Section: Discussionmentioning
confidence: 99%
“…Comunian, Custódio et al, 32 compared the effects of low-level lasers with LED. For this experiment 18 rabbits were divided into 3 groups.…”
Section: Discussionmentioning
confidence: 99%